2010
DOI: 10.1111/j.1365-2478.2010.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards quantitative evaluation of gas injection using time-lapse seismic data

Abstract: A B S T R A C TOf particular concern in the monitoring of gas injection for the purposes of storage, disposal or improved oil recovery is the exact spatial distribution of the gas volumes in the subsurface. In principle this requirement is addressed by the use of 4D seismic data, although it is recognized that the seismic response still largely provides a qualitative estimate of moved subsurface fluids. Exact quantitative evaluation of fluid distributions and associated saturations remains a challenge to be so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Fehmers et al (2007) demonstrate that the apparent time shifts that result from misalignment are azimuthally dependent, with the largest shifts occurring in the di rection of the positioning error. That often results in a more consistent positioning solution, which can also provide a better 3D image.…”
Section: Baseline-survey Navigation Qualitymentioning
confidence: 85%
“…Fehmers et al (2007) demonstrate that the apparent time shifts that result from misalignment are azimuthally dependent, with the largest shifts occurring in the di rection of the positioning error. That often results in a more consistent positioning solution, which can also provide a better 3D image.…”
Section: Baseline-survey Navigation Qualitymentioning
confidence: 85%
“…This is because for CO 2 projects such as at the Sleipner or Snøhvit fields or methane injection at An'Teallach (Falahat et al . ), thick subsurface intervals of 200–300 m are saturated at maximum gas saturation resulting in significant slowdowns of up to 20 ms. Pressure increase helps to exaggerate the impact of this effect. Moderate slowdown effects of up to 12 ms are also observed due to steam injection into heavy oil or injection of Enhanced Oil Recovery (EOR) solvents. Reservoir gas liberated from solution by pressure drop below bubble point (Svale in Fig. b, also for example the Emeraude, Baobab or Schiehallion fields) is observed to also exhibit a more moderate range of slowdowns of up to 10 ms, as the gas tends to occupy most of the reservoir volume at the critical gas saturation (Falahat et al .…”
Section: The Magnitude Of 4d Seismic Time‐shiftsmentioning
confidence: 99%
“…Hall et al 2002;Hatchell and Bourne 2005a) but increasingly also for assessing fluid saturation variations (e.g. Falahat, Shams and MacBeth 2010). Velocity changes associated with time-shifts are considered to be long wavelength in nature if they correspond to stress/strain changes due to depletion or injection in the reservoir, but are more localized when influenced by fluid saturation and contact movement.…”
Section: Introductionmentioning
confidence: 99%
“…This is the proper physical choice for both pressure and saturation, a fact well-known in fundamental engineering literature (for example, Dake 2002). Indeed, some evidence exists to indicate that volumes in general ('total fluid' or 'pore') are an important control on the 4D seismic signatures -for example, it has been recently shown that 4D seismic signatures are strongly correlated to well volume changes (Falahat, Shams and MacBeth 2011;Huang et al 2011). These arguments suggest the application of the principle of adaptive scaling to the principal parameters controlling the 4D seismic signature.…”
Section: Relating Pressure and Saturation Change To The 4d Seismic Simentioning
confidence: 96%